Ittila'iyah dar mahkumyyati iqdamati inshi'abtalabanahi-yi firaksyuni hakim bar daftari syasi (Sazmani Kargarani Inqilabi-yi Iran (Rahi Kargar))
A statement in condemnation of the schism of the faction governing the political bureau.